Occurrence of Low Value Bycatch in Trawl Fisheries off Karnataka, India - Mahesh, V.; Benakappa, S.; Dineshbabu, A. P.; Kumar Naik, A. S.; Vijaykumar, M. E.; Khavi, Muttappa (Fishery Technology, 2017)
Bottom trawling in the most effective method of shrimp capture but highly intensive trawling adversely affects benthic ecology and biodiversity. The present study is aimed to throw light on low value bycatch (LVB) landings and catch composition of trawl boats, at Mangaluru fisheries harbour. The quantity of fish landings by single day trawlers (SDT) during 2012-14 was 2 151.3 t y-1, of which 61.8% was considered as edible grade and 38.2% was LVB. Multiday trawlers (MDT) landed an estimated 165917.2 t of fishes/yr, out of which 79.6% were marked for edible use and remaining 20.4% was landed as LVB. LVB to target group ratio for SDT and MDT landings was 1:1.66 and 1:3.93, respectively. The LVB of MDT consisted of 121 finfishes belonging to 82 genera, 55 families and 13 orders. An estimated 47.53% of the finfish LVB landing by weight (56.1% by number) was contributed by juveniles of commercially important species and the estimated resource loss was 14044 t by weight and 11000 million in number. From the fishery resource conservation and sustainability point of view, the magnitude of resource damage due to trawl bycatch is alarmingly increasing. The study recommends using trawl nets with 35 mm square mesh codend, effort reduction in critical fishing grounds and adoption of Juvenile Fish Excluder cum Shrimp Sorting Device (JFE-SSD) which minimizes juvenile fish catch.